The ranking destination areas for land consolidation works, due to the size checkerboard land on the example of Białaczów - Leń, Przemysław (International Conference “Environmental Engineering”, 2017)
The aim of this paper was to analyze the degree of fragmentation of the checkerboard of land ownership to determine a priority ranking of areas intended for land consolidation in the commune of Białaczów, the Łódź Province (Voivodeship). For a village to be qualified for land consolidation, according to the Act of 26 March 1982 on the Consolidation and Exchange of Land (Official Journal of Laws of 2003, no 178, item 1749, as amended), more than 50% of land owner signatures have to be obtained. On the other hand, the guiding principle for the qualification of a village for a land merger, within the framework of a consolidation program, is that the highest percentage of owners accede to the program. A common obstacle to collecting signatures from landowners is that some of them live outside the village concerned (non-resident owners). The aim of this article was to identify those villages in which land consolidation was an urgent priority.